INTERVAL PREDICTION OF NON-STATIONARY PROCESSES, DESCRIBED BY STOCHASTIC DIFFERENTIAL EQUATIONS WITH VARIABLE PARAMETERS - A. V. Ausiannikau (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The task of interval prediction of non-stationary processes of stochastic differential equations described by models with variable parameters is considered. Algorithms of interval prediction in the discrete and continuous time are received. Questions of achievement of boundaries and temporal adequacy of prognostic model are analyzed.